2020
DOI: 10.3892/mco.2020.2003
|View full text |Cite
|
Sign up to set email alerts
|

Association between functional TERT promoter polymorphism rs2853669 and cervical cancer risk in South Indian women

Abstract: A single nucleotide polymorphism (SNP) rs2853669 (A>G) in the telomerase reverse transcriptase (TERT) promoter has recently been reported in chr5:1,295,349 T>C (T349C), and was shown to be associated with increased cancer risk and poor survival in a specific population. However, at present, the role of this particular SNP with TERT promoter driver mutations and its genetic association with human papilloma virus (HPV) in patients with cervical cancer has not been determined. In the present study, the genetic as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…A previous study found TERT T349C to be present in 52% of melanoma cell lines ( 43 ). The high frequency of T349C also aligns with previous studies on other cancers ( 70 72 ). All the TERT promoter mutations C228T and C250T and 14/17 (82%) BRAF/NRAS mutations co-occurred with the germline TERT promoter variant T349C ( Figure 2 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A previous study found TERT T349C to be present in 52% of melanoma cell lines ( 43 ). The high frequency of T349C also aligns with previous studies on other cancers ( 70 72 ). All the TERT promoter mutations C228T and C250T and 14/17 (82%) BRAF/NRAS mutations co-occurred with the germline TERT promoter variant T349C ( Figure 2 ).…”
Section: Resultssupporting
confidence: 90%
“…This TERT SNP has been identified in a range of other cancers and may act to disrupt a pre-existing ETS binding site in the TERT promoter ( 81 ). Nevertheless, its prognostic role remains controversial with contrasting reports on its influence on TERT expression and differing conclusions on its prognostic value ( 43 , 70 72 , 82 , 83 , 85 88 ). In melanoma, TERT T349C has been reported to modify the effects of somatic TERT promoter mutations leading to increased survival in melanoma ( 40 ) and this may be mediated through a lengthening of telomeres ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…It obstructs an ETS2 binding site, located close to an E-box. Previous studies showed that TERTp mutations creating a putative binding site for ETS, resulted in TERT upregulation and increased telomerase activity, while mutations at the ETS2 binding site suppressed c-MYC binding to the E-box ( 146 , 147 ). Studies on rs2853669 showed that it is significantly associated with poor survival and increased cancer risk rate in hepatocellular carcinoma patients ( 146 ).…”
Section: Tert Gene Polymorphismsmentioning
confidence: 99%
“…Previous studies showed that TERTp mutations creating a putative binding site for ETS, resulted in TERT upregulation and increased telomerase activity, while mutations at the ETS2 binding site suppressed c-MYC binding to the E-box ( 146 , 147 ). Studies on rs2853669 showed that it is significantly associated with poor survival and increased cancer risk rate in hepatocellular carcinoma patients ( 146 ). In contrast, it was also observed to correlate with improved survival in patients with clear cell renal cell carcinoma, melanoma and glioblastoma ( 148 ).…”
Section: Tert Gene Polymorphismsmentioning
confidence: 99%
“…Nevertheless, alterations in regulatory regions are associated with many complex traits (Deplancke et al, 2016). Particularly, there are recurrent functional mutations in regulatory regions (Saini and Gordenin, 2018), such as the well-studied recurrent C>T transition that creates a strong binding site for the GABP transcription factor in the TERT promoter and is associated with increased cancer risk (Bell et al, 2015;Horn et al, 2013;Vinothkumar et al, 2020). Somatic mutations are caused by a combination of DNA damage and DNA repair failures (Volkova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%